2019
DOI: 10.1088/1748-0221/14/05/p05008
|View full text |Cite
|
Sign up to set email alerts
|

Studies of granularity of a hadronic calorimeter for tens-of-TeV jets at a 100 TeV pp collider

Abstract: Jet substructure variables for hadronic jets with transverse momenta in the range from 2.5 TeV to 20 TeV were studied using several designs for the spatial size of calorimeter cells. The studies used the full Geant4 simulation of calorimeter response combined with realistic reconstruction of calorimeter clusters. In most cases, the results indicate that the performance of jet-substructure reconstruction improves with reducing cell size of a hadronic calorimeter from ∆η × ∆φ = 0.087 × 0.087, which are similar t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…However, a further increase of the η granularity of the HB is not improving the jet angular resolution significantly which supports the choice for the reference detector design. Studies of the cell granularity of the hadronic calorimeter, optimised for jet substructure variable, have shown similar results [53] and support the chosen granularity of ∆η × ∆φ = 0.025 × 0.025 for the hadronic calorimeter. Including more sophisticated jet reconstruction techniques like particle flow algorithms or DNNs could be however more sensitive to the granularity and thus point into another direction.…”
Section: Angular Resolutionsmentioning
confidence: 54%
“…However, a further increase of the η granularity of the HB is not improving the jet angular resolution significantly which supports the choice for the reference detector design. Studies of the cell granularity of the hadronic calorimeter, optimised for jet substructure variable, have shown similar results [53] and support the chosen granularity of ∆η × ∆φ = 0.025 × 0.025 for the hadronic calorimeter. Including more sophisticated jet reconstruction techniques like particle flow algorithms or DNNs could be however more sensitive to the granularity and thus point into another direction.…”
Section: Angular Resolutionsmentioning
confidence: 54%
“…Thanks to the superior tracker segmentation, we find Track-jets to perform better in terms of QCD background rejection despite the slightly worse jet mass resolution. A recent study shows that the reconstruction of jet substructure variables for highly boosted objects will benefit from small cell sizes of the hadronic calorimeter which confirms the FCC baseline design [57].…”
Section: Calorimetry and Particle-flowmentioning
confidence: 66%
“…There are several detector technologies that will improve JSS and related techniques. These include finer calorimeter granularity [127,128], more hermetic coverage of tracking detectors, and precise measurements of timing information. The experience of the LHC has shown that such information can be used to more accurately reconstruct the interaction of hadrons with various detector elements, much of which is used in the "particle flow" (PF) [129] concept already deployed by the LHC experiments.…”
Section: Detector Optimizationmentioning
confidence: 99%